A vocational education program for the Lower Rio Grande Valley of Texas, based upon needs - Edwards, Hamp S., author; Hinderman, Roy Aaron, 1900-, advisor; Yingling, J. B., committee member; Williams, E. L., committee member; Betts, Gilbert L., committee member; Frasier, P. G., committee member; Newsom, Isaac Ernest, 1883-1954, committee member; Kezer, Alvin, 1877-, committee member (Colorado State University. Libraries, 1939)
To view the abstract, please see the full text of the document.
Keywords: Vocational education -- Texas